Passive energy balancing design for a linear actuated morphing wingtip structure - Jiaying Zhang (Aerospace Science and Technology, 2020)
A passive energy balancing concept for linear actuation is investigated in the current work by adopting a negative stiffness mechanism. The proposed negative stiffness mechanism uses a pre-tensioned spring to produce a passive torque and therefore to transfer the passive torque through a crankshaft for linear motion.The proposed passive energy balancing design is supposed to be applied in a morphing wingtip, of which the shape change comes from the elastic deformation of the morphing structure. A significant amount of linear actuation force can be required to deform the structure, and therefore it is important to reduce the required force and the consumed energy by adopting the passive energy balancing design.The kinematics of the negative stiffness mechanism is developed to satisfy the required linear motion and its geometry is then optimised to reduce the energy requirements. The performance of the optimised negative stiffness mechanism is evaluated through the net force and the total required energy, which shows the potential of the design in the morphing wingtip application.